1973
DOI: 10.1002/jmor.1051410302
|View full text |Cite
|
Sign up to set email alerts
|

The hemocytes of a millipede, Thyropygus poseidon

Abstract: Some of the cytological and histochemical characteristics of hemocytes of Thyropygus poseidon were studied. Jone's system of classification of hemocytes was extended to millipede hemocytes. Seven classes were identified as prohemocytes, plasmatocytes, granular hemocytes, cytocytes, oenocytoids, spherule cells and adipohemocytes. Oenocytoids were rarely found. All cells except prohemocytes and oenocytoids sequestered oxidized products of catechol. Results of the histochemical tests for proteins also suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…In L. forficatus, five types of hemocytes have been found within the hemolymph (Nevermann et al. ), while in other centipedes three types mainly occur: prohemocytes, plasmatocytes, and granulocytes (Ravindranath ; Nevermann et al. ; Hilken et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In L. forficatus, five types of hemocytes have been found within the hemolymph (Nevermann et al. ), while in other centipedes three types mainly occur: prohemocytes, plasmatocytes, and granulocytes (Ravindranath ; Nevermann et al. ; Hilken et al.…”
Section: Discussionmentioning
confidence: 99%
“…In chilopods, hemocytes have also been described as cells responsible for the protection of the midgut epithelium against an invasion of pathogens (Bowen 1968;Nevermann et al 1991;Xylander 1992). In L. forficatus, five types of hemocytes have been found within the hemolymph (Nevermann et al 1991), while in other centipedes three types mainly occur: prohemocytes, plasmatocytes, and granulocytes (Ravindranath 1973;Nevermann et al 1991;Hilken et al 2003;Xylander & Nevermann 2006;Xylander 2009a). Hemocytes have been observed between visceral muscle fibers, beneath the basal lamina, and within the midgut epithelium between digestive cells in L. forficatus; according to the literature on classification of chilopod hemocytes, these cells are probably granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Histochemistry. A number of authors have characterized the granules histochemically (Hoffmann, 1967;Ravindranath, 1973Ravindranath, , 1975FranGois, 1974;Costin, 1975). Hoffmann (1967) observed that the granules of cystocytes are periodic acid-Schiff (PAS)-positive after amylase treatment, Alcian blue-positive and exhibit pyridine-labile sudanophilia.…”
Section: I43mentioning
confidence: 99%
“…In arthropods in general, haemocytes have been classified into as many as seven types. The classification and nomenclature proposed by Jones (1962) for insect haemocytes appears suitable also for arthropods of other groups (Sherman, 1973 ;Ravindranath, 1973Ravindranath, ,1974a, b, 1 9 7 5~; Gupta, 1979). The following are the haemocytes commonly seen in arthropods : prohaemocytes, plasmatocytes, granular haemocytes, cystocytes, spherule cells and adipohaemocytes.…”
mentioning
confidence: 99%
“…The haemocytes can be defined as a mixture of types of cells with different morphologies and biological functions (Falleiros et al 2003). Studies about the diplopods haemocytes are scarce; the first work carried out in this sense was with the milliped Thyropygus poseidon (Ravindranath 1973), in which the author compared the types of haemocytes found in this species with the classification carried out by Jones (1962) for insects haemocytes.…”
Section: Discussionmentioning
confidence: 98%